Field-scale bioremediation of arsenic-contaminated groundwater using sulfate-reducing bacteria and biogenic pyrite. Issue 1 (2nd January 2019) - Lee, Ming-Kuo; Saunders, James A.; Wilson, Theodore; Levitt, Eric; Saffari Ghandehari, Shahrzad; Dhakal, Prakash; Redwine, James; Marks, Justin; Billor, Zeki M.; Miller, Brian; Han, Dong; Wang, Luxin
Abstract: This research demonstrates that biogenic pyrite formed by stimulation of indigenous sulfate-reducing bacteria (SRB) in a natural aquifer can remove dissolved arsenic from contaminated groundwater under strongly reducing conditions. SRB metabolism led to the precipitation of biogenic pyrite nanoparticles capable of sorbing and co-precipitating arsenic. The field site is an industrial site where shallow groundwater in an unconfined sandy aquifer is contaminated by arsenic. Therefore, biodegradable organic carbon, ferrous iron, sulfate, and fertilizer were injected into groundwater and SRB metabolism began about 1 week later. Microscopic, X-ray diffraction, X-ray fluorescence, and electron microprobe analyses confirm the bio-mineralization of pyrite and over time, pyrite nanoparticles grew to form well-formed crystals (1–10 µm in diameter) or spherical aggregates that contain 0.05–0.4 wt. % arsenic, indicative of their capacity to sequester arsenic. Consequently, dissolved arsenic decreased from its initial concentration of 0.3–0.5 mg/L to below the regulatory clean-up standard for the site of 0.05 mg/L in three downgradient wells in a matter of weeks after injection. The main sequestration stage, with total arsenic removal rates greater than 90%, lasted for at least 6 months until the arrival and mixing of untreated groundwater from upgradient. Treated groundwater with most active bacterial sulfate reduction became enriched in heavy 34 S (range from 2.02 to 4.00 ‰) compared to unaffected well water (0.40–0.61 ‰). One to three orders of magnitude increases in SRB cells were observed in treated wells for at least 2 months after injection. For a full-scale remediation, the injection of solution should start at positions hydrologically upgradient from the major plume and proceed downgradient. If needed, aquifers may be repeatedly amended with biodegradable organic carbon to reestablish the reducing conditions that favor arsenic sequestration.